2017
DOI: 10.1159/000485013
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Cooperates with CREB Binding Protein to Promote the Growth of Tumor Cells

Abstract: Background/Aims: β-catenin is an integral component of the canonical Wnt signaling pathway, and its mutations are an autosomal recessive cause of colorectal cancer (CRC), medulloblastoma (MDB), and ovarian cancer. Nevertheless, little is known about its function in lung cancers. Methods: We first knocked down β-catenin by siRNA to investigate its effects on lung cancer cell proliferation, migration and apoptosis. Then we verified the interaction between β-catenin and CREB binding protein (CBP) by immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Studies in mice have demonstrated that Lgr5 might be another marker of both normal colon stem cells and colon CSCs [37]. Indeed, Lgr5 is a member of the Wnt/β-catenin pathway, which plays a key role in maintaining CSC self-renewal and tumorigenic ability [9, 13, 38, 39]. Kemper et al isolated a distinct subpopulation of EpCAM+Lgr5+ cells from primary human colorectal cancer cells and confirmed that Lgr5 overexpression induced the malignant cancer profile [9].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have demonstrated that Lgr5 might be another marker of both normal colon stem cells and colon CSCs [37]. Indeed, Lgr5 is a member of the Wnt/β-catenin pathway, which plays a key role in maintaining CSC self-renewal and tumorigenic ability [9, 13, 38, 39]. Kemper et al isolated a distinct subpopulation of EpCAM+Lgr5+ cells from primary human colorectal cancer cells and confirmed that Lgr5 overexpression induced the malignant cancer profile [9].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/ β ‐catenin signaling pathway, according to previous studies, could promote cancer cell proliferation and migration and be down‐regulated by several members of HECT domain‐containing E3 ligases like Huwe1 . Given these studies, we assume that HACE1, one member of the HECT family, might also target the Wnt pathway to regulate cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 82%
“…(i) Inhibitors of β-catenin transcriptional activity β-Catenin/CBP binds to WRE (Wnt-responsive element; 5′-CTTTGA/TA/T-3′) and activates target gene transcription 101,102 . PRI-724 (ICG-001; NIH clinical trial numbers: NCT01302405, NCT02413853, NCT01764477, and NCT01606579) inhibits the interaction between CBP and β-catenin and prevents transcription of Wnt target genes 103 .…”
Section: (I) Porcn Inhibitors Wnt974 (Lgk974; Nih Clinical Trial Numbmentioning
confidence: 99%